IMPACT EVALUATION OF SOUTH AFRICA'S MANDATORY SALT LEGISLATION. (April 2021) - Charlton, Karen; Kowal, Paul; Ware, Lisa; Schutte, Alta; Corso, Barbara; Minicuci, Nadia
Abstract : Objective: South Africa implemented legislation in June 2016 mandating maximum sodium (Na) levels in a range of processed foods. A pre-post impact evaluation was undertaken to assess whether the legislative approach reduced salt intake and blood pressure in South Africans. Design and method: Baseline sodium intake was assessed in a nested cohort of the WHO Study on global AGEing and adult health (WHO-SAGE) Wave 2 (W2; 2014–2015). From 4030 randomly selected households, 24 h urine samples were collected in a random subsample (n = 1200) for Na potassium (K), creatinine and iodine analysis, alongside blood pressure (BP) and anthropometric measures. Follow-up in Wave 3 (W3; 2018) included replacements in the case of non-compliance or loss to follow-up. Complete urine collections were determined as volume > 300 mL and creatinine excretion > = 4 mmol/day (women) or > = 6 mmol/day (men). Results: Median salt intake indicated a slight downward trend between W2 (median 6.6 (IQR 6.1) g salt/day; n = 408) and W3 (6.3 (5.4) g/day; n = 392); with borderline significance (P = 0.0924). Proportion meeting the salt target of < 5 g/day remained similar (33.3 vs 34.7%; P = 0.685). In n = 48 paired subjects with complete urine and survey data in both waves, a non significant downward trend in salt intake was observed (median 6.7 (4.3) to 6.1 (5.4) g/day); P = 0.644). Significant predictors for increased systolic BP pressure between W2 and W3 were hypertension status (p < 0.0001) and age (p = 0.002). Conclusions: Complexities of obtaining repeat measures in the same individuals over 3 years of follow-up prevents determination of the magnitude of change in salt intake. These first results of salt intake following implementation of South Africa's mandatory sodium legislation, using valid 24hr urinary Na concentrations in a national sample suggest that the phased approach whereby stricter Na levels were enforced from June 2019 is necessary to achieve predicted population salt reduction of 0.85 g salt/person.